Echoes of an epic [videorecording] life imitates art in Maranao country - Medina, Susan Calo; Quintos, Floy (Travel Time, 1995)
A documentary on the Maranaos of Marawi, Lanao del Sur. It features the Darangan, the epic of the Maranao which speaks of their history and culture. Tackles Maranao malong and its use.